2008
DOI: 10.1177/089686080902900211
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Children on Peritoneal Dialysis

Abstract: Objectives Enhanced oxidative stress has been observed in dialysis and predialysis adult patients with chronic kidney disease (CKD), which resulted in increased mortality and morbidity within this population. Not much attention in the literature has been paid to nonenzymatic antioxidant defense in children with CKD on peritoneal dialysis (PD). The aim of the present study was to describe the plasma, erythrocyte, and dialysate concentrations of oxidized (GSSG) and reduced glutathione (GSH) and vitamins A, E, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
0
10
0
3
Order By: Relevance
“…Moreover, PD patients presented a pronounced deficiency of antioxidants, as expressed by lower serum levels of ascorbic acid, vitamin E, and glutathione when compared to the control group [ 25 ]. Zwolinska et al found that children on PD had reduced activity of GSH in RBCs and plasma and significantly decreased levels of antioxidant vitamins A, C, and E—due to loss of these vitamins into the ultrafiltrate—compared to age-matched healthy controls [ 26 ].…”
Section: Os Status In Pdmentioning
confidence: 99%
“…Moreover, PD patients presented a pronounced deficiency of antioxidants, as expressed by lower serum levels of ascorbic acid, vitamin E, and glutathione when compared to the control group [ 25 ]. Zwolinska et al found that children on PD had reduced activity of GSH in RBCs and plasma and significantly decreased levels of antioxidant vitamins A, C, and E—due to loss of these vitamins into the ultrafiltrate—compared to age-matched healthy controls [ 26 ].…”
Section: Os Status In Pdmentioning
confidence: 99%
“…Furthermore, since various pro-inflammatory cytokines were promoted due to metabolic acidosis [ 12 ], volume overload [ 13 ], and non-sterile dialysate [ 14 ], patients were usually on mirco-inflammation status [ 15 , 16 ]. On the other side, antioxidant levels, such as plasma vitamin C level and reduced glutathione level, were usually decreased [ 3 , 5 , 17 , 18 ]. It was documented that inflammation was associated with increased risk of cardiovascular morbidity and mortality in patients on dialysis [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data are in agreement with previous studies including individuals with benign hyperbilirubinemia who also possess significantly elevated GSH and SH concentrations compared to controls, the concentration of which was positively correlated with unconjugated bilirubin (UCB) concentrations 37 43 . The glutathione antioxidant system is regarded as an important marker of oxidative stress in chronic kidney disease 44 45 . Previous studies have shown that the uraemic state is associated with low concentrations of GSH and reduced thiols (SH), which continue to decrease with the progression of kidney failure in dialysis patients 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The glutathione antioxidant system is regarded as an important marker of oxidative stress in chronic kidney disease 44 45 . Previous studies have shown that the uraemic state is associated with low concentrations of GSH and reduced thiols (SH), which continue to decrease with the progression of kidney failure in dialysis patients 45 . Our findings, therefore, may indicate that bilirubin plays an important role in maintaining circulating thiol status providing an important pool of antioxidant capacity, which can protect proteins and lipids from oxidation by oxidants produced during inflammation, namely hypochlorous acid produced from myeloperoxidase (MPO) 46 .…”
Section: Discussionmentioning
confidence: 99%